Strengthening Character Education through Islamic Education in the Era of Industrial Revolution 4.0 - Wahib, Ahmad; Nafi’ah, Ayu Zahroh; Abidin, Riadil (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
Humans must improve morale and intelligence when more complex technologies are developed. An intellectual and morally honest generation most are the result of education. The foundation of Islamic religious education is tp establish itself as a sources of real power that can lead to the desired action, namely character development in the era of the digital revolution. This research uses qualitative methodology and forms of literature research. Books, research journals, and seminar procceedings are studies as primary sources by researchers. According to this literature survey, Islamic religious education bases its character development program on religion. Islamic religious education prioritizes morality (character) in students through teaching, habituation, coercion and punishment.